Pelanggaran Administrasi yang Terstruktur Masif dan Sistematis dalam Pemilihan Kepala Daerah: Bagaimana Prosedur Penanganan dan Konstruksi Hukumnya? - Ahmad Jukari (AL-BURHAN, 2022)
The election of governors and deputy governors, regents and deputy regents, and/or mayors and deputy mayors is regulated in Law (UU) Number 1 of 2015 as amended by Law Number 8 of 2015, Law Number 10 of 2016, and Law Number 6 of 2020 (Election Law). The Election Law regulates administrative sanctions for the cancellation of regional head candidates who commit massive and systematic structured administrative violations in the implementation of elections. In its application, there are different perspectives between Bawaslu, KPU, and the Supreme Court. This can be observed in the decision of the Supreme Court through the decision Number 1 P/PAP/2021, the Bawaslu of Lampung Province through the Decision Number 02/Reg/L/TSM-PW/08.00/XII/- 2020, and the KPU Bandar Lampung City through Decision Number 007. /HK.03.1-Kpt/1871/- KPU-Kot/I/2021.